Exclusive color-coded duplex sonography of extracranial vessels reliably confirms brain death: A prospective study - Lambeck, Johann; Strecker, Christoph; Niesen, Wolf-Dirk; Bardutzky, Jürgen (Frontiers in Neurology, 2022)
Background Transcranial color-coded duplex sonography (TCCD) can be used as an ancillary test for determining irreversible loss of brain function (ILBF) when demonstration of cerebral circulatory arrest (CCA) is required. However, visualization of the intracranial vessels by TCCD is often difficult, or even impossible, in this patient cohort due to elevated intracranial pressure, an insufficient transtemporal bone window, or warped anatomical conditions. Since extracranial color-coded duplex sonography (ECCD) can be performed without restriction in the aforementioned situations, we investigated the feasibility of omitting TCCD altogether, such that the ILBF examination would be simplified, without compromising on its reliability. Methods A total of 122 patients were prospectively examined by two experienced neurointensivists for the presence of ILBF from 01/2019-12/2021. Inclusion criteria were (i) the presence of a severe cerebral lesion on cranial CT or MRI, and (ii) brainstem areflexia. Upon standardized clinical examination, 9 patients were excluded due to incomplete brainstem areflexia, and a further 22 due to the presence of factors with a potentially confounding influence on apnea testing, EEG or sonography. A total of 91 patients were enrolled and underwent needle-EEG recording for >30 min (= gold standard), as well as ECCD and TCCD. The sonographer was blinded to the EEG result. Results All patients whose ECCD result was consistent with ILBF had this diagnosis confirmed by EEG (n = 77; specificity: 1). Both ECCD and EEG were not consistent with ILBF in a further 12 patients. In the remaining two patients, ECCD detected reperfusion due to long-lasting cerebral hypoxia; however, ILBF was ultimately confirmed by EEG (sensitivity: 0.975). This yielded a positive predictive value (PPV) of one and a negative predictive value of 0.857 for the validity of ECCD in ILBF confirmation. TCCD was not possible/inconclusive in 31 patients (34%). Conclusions The use of ECCD for the confirmation of ILBF is associated with high levels of specificity and a high positive predictive value when compared to needle-electrode EEG. This makes ECCD a potential alternative to the ancillary tests currently used in this setting, but confirmation in a multi-center trial is warranted. Trial registration https://www.drks.de, DRKS00017803.